Minimally invasive thymectomy for myasthenia gravis favours left-sided approach and low severity class. (4th February 2021) - Wilshire, Candice L; Blitz, Sandra L; Fuller, Carson C; Rückert, Jens C; Li, Feng; Cerfolio, Robert J; Ghanim, Asem F; Onaitis, Mark W; Sarkaria, Inderpal S; Wigle, Dennis A; Joshi, Vijay; Reznik, Scott; et al.
Abstract: : OBJECTIVES: Complete thymectomy is a key component of the optimal treatment for myasthenia gravis. Unilateral, minimally invasive approaches are increasingly utilized with debate about the optimal laterality approach. A right-sided approach has a wider field of view, while a left-sided approach accesses potentially more thymic tissue. We aimed to assess the impact of laterality on perioperative and medium-term outcomes, and to identify predictors of a 'good outcome' using standard definitions. METHODS: We performed a multicentre review of 123 patients who underwent a minimally invasive thymectomy for myasthenia gravis between January 2000 and August 2015, with at least 1-year follow-up. The Myasthenia Gravis Foundation of America standards were followed. A 'good outcome' was defined by complete stable remission/pharmacological remission/minimal manifestations 0, and a 'poor outcome' by minimal manifestations 1–3. Univariate and multivariable logistic regression analyses were performed to assess factors associated with a 'good outcome'. RESULTS: Ninety-two percent of thymectomies (113/123) were robotic-assisted. The left-sided approach had a shorter median operating time than a right-sided: 143 (interquartile range, IQR 110–196) vs 184 (IQR 133–228) min, P = 0.012. At a median of 44 (IQR 27–75) months, the left-sided approach achieved a 'good outcome' (46%, 31/68) more frequently than the right-sided (22%, 12/55); P = 0.011. Multivariable analysis identified a left-sided approach and Myasthenia Gravis Foundation of America class I/II to be associated with a 'good outcome'. CONCLUSIONS: A left-sided thymectomy may be preferred over a right-sided approach in patients with myasthenia gravis given the shorter operating times and potential for superior medium-term symptomatic outcomes. A lower severity class is also associated with a 'good outcome'.